Development of a Shooter Game Control System on a Desktop-Based Interface Using Arduino Uno and IMU Sensors: Pengembangan Sistem Kendali Game Shooter Pada Interface Berbasis Desktop Menggunakan Arduino Uno dan Sensor IMU - Hafazah Kano Sukamto; Kezia Vallerie Hartono; Sevtian Bintang Yoda; Tiara Satyawira Pratiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2023)
Currently there are various control systems available that can be used for games that can increase user interaction with the game being played. The use of this control system utilizes interface technology to facilitate user interaction. With a control system and an easy-to-use interface, the games that are presented will be more interesting and fun to play. The research was conducted with the aim of developing an interactive control system for shooter games on a desktop interface using Arduino Uno and IMU sensors. The research was developed using the Arduino Uno hardware connected to the IMU sensor and then integrated with the Arduino IDE as the main control for camera rotation and the user's point of view in the game interface. After conducting several experiments on users, the research concluded that the Arduino Uno device is easy to use as a control system with appropriate camera rotation and a clearly visible game interface.